Diffusion Tensor Imaging Screening of Radiation-Induced Changes in the White Matter after Prophylactic Cranial Irradiation of Patients with Small Cell Lung Cancer: First Results of a Prospective Study - Welzel, T.; Niethammer, A.; Mende, U.; Heiland, S.; Wenz, F.; Debus, J.; Krempien, R. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Diffusion tensor imaging (DTI) will show abnormal fractional anisotropy (FA) in the normal-appearing brain after prophylactic cranial irradiation (PCI). These abnormalities will be more accentuated in patients with underlying vascular risk factors.MATERIALS AND METHODS: A prospective study by use of DTI and conventional T2-weighted MR images was performed with a 1.5T unit with 16 patients with small cell lung cancer and undergoing PCI. All of the T2-weighted images were evaluated with respect to abnormalities in signal intensity of white matter as markers of radiation damage. Measurements of FA were performed before, at the end of, and 6 weeks after radiation therapy. On the FA maps, the bifrontal white matter, the corona radiata, the cerebellum, and the brain stem were evaluated. FA values were compared with respect to age, demographic, and vascular risk factors. Statistical analyses (Friedman test, Wilcoxon test, and Mann-Whitney U test) were performed.RESULTS: Fractional anisotropy decreased significantly in supratentorial and infratentorial normal-appearing white matter from the beginning to the end of PCI (P < .01). A further decline in FA occurred 6 weeks after irradiation (P < .05). A stronger reduction in FA was observed in patients with more than 1 vascular risk factor. There was an age-related reduction of white matter FA. Patients 65 years and older showed a trend toward a stronger reduction in FA.CONCLUSION: During the acute phase, after PCI, patients with many vascular risk factors showed stronger damage in the white matter compared with patients with only 1 risk factor.